2014
DOI: 10.3892/or.2014.3547
|View full text |Cite
|
Sign up to set email alerts
|

Annexin A5 inhibits diffuse large B-cell lymphoma cell invasion and chemoresistance through phosphatidylinositol 3-kinase signaling

Abstract: Diffuse large B-cell lymphoma (DLBCL) is the most common type of non-Hodgkin's lymphoma worldwide. Although patient outcomes have significantly improved to a greater than 40% cure rate by the combinatorial cyclophosphamide, doxorubicin, vincristine and prednisone (CHOP) chemotherapy, which is widely used, resistance to the CHOP regimen continues to pose a problem in managing or curing DLBCL. While it promotes the malignancy and chemo-resistance in certain types of cancer, Annexin A5 is negatively correlated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 25 publications
0
17
1
Order By: Relevance
“…Caspase 3 activity, which is present in the high activity of apoptotic cells in the caspase enzyme [13], confirmed the results of this study indicate that inhibition MALAT1 OGD-Rinduced apoptosis in human brain microvascular endothelial cells. OGD-R has been reported to overproduce ROS cells, leading to apoptosis [15][16][17][18][19]. In this study, OGD-R was shown to significantly increase cellular ROS content.…”
Section: Discussionmentioning
confidence: 54%
“…Caspase 3 activity, which is present in the high activity of apoptotic cells in the caspase enzyme [13], confirmed the results of this study indicate that inhibition MALAT1 OGD-Rinduced apoptosis in human brain microvascular endothelial cells. OGD-R has been reported to overproduce ROS cells, leading to apoptosis [15][16][17][18][19]. In this study, OGD-R was shown to significantly increase cellular ROS content.…”
Section: Discussionmentioning
confidence: 54%
“…As described previously (11), the activation of Akt1, the downstream effector of the PI3K, was significantly inhibited by BMK210. CHOP-induced cytotoxicity was decreased in rPD-1-treated cells, but this effect was abolished by the application of BMK210.…”
Section: Discussionmentioning
confidence: 89%
“…PD-1 binds to 2 ligands, PD-L1 and PD-L2, belonging to the B7 family (6). PD-L1 is expressed in DLBCL cells, including CRL2631 (9,11). To examine the role of PD-1/PD-L1 axis in CHOP-induced CRL2631 injury, the expression of PD-L1 was knocked down by introducing the validated siRNA that specifically targets to human PD-L1 (14).…”
Section: Pd-1/pd-l1 Interaction Decreases the Cytotoxic Effects Of Chmentioning
confidence: 99%
“…It has been reported that OGD-R induces cellular overproduction of ROS, which leads to cell apoptosis (1519). In the present study, it was revealed that OGD-R significantly increased cellular ROS content.…”
Section: Discussionmentioning
confidence: 99%